Evergreen oak leaves as natural monitor in environmental pollution (Journal of radioanalytical and nuclear chemistry, 1988)
Evergreen oak was chosen as a possible biological monitor of environmental pollution. It was shown that there is a direct relationship between the concentration of elements in leaves and the presence of pollution sources, i.e. the density of vehicular traffic.